Reconstruction of Chronic Monteggia Fracture with Radial Head Excision: A Case Report - Baharuddin, Nur Khumaira; Andi Dhedie Prasatia Sam; Fadil Mula Putra (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Chronic Monteggia fracture is a rare and clinically challenging condition, characterized by a non-union fracture of the proximal ulna with dislocation of the radial head. This case report presents the case of a 42-year-old woman with a chronic Monteggia fracture diagnosed 21 years after the initial injury, highlighting the importance of a careful patient history and radiographic investigation. Case presentation: A 42-year-old woman presented with left elbow pain and a history of significant trauma 21 years previously. Physical examination revealed limited range of motion and radiographic examination revealed a nonfused fracture of the proximal ulna with dislocation of the radial head. The patient underwent open reduction and internal fixation (ORIF) reconstruction of the ulna and excision of the radial head. Conclusion: Successful surgical reconstruction of chronic Monteggia fractures results in significant improvements in the patient's function and quality of life. This case report emphasizes the importance of early diagnosis and timely surgical intervention to prevent long-term complications and achieve optimal functional outcomes.